Integrasi Otomatisasi Evaluasi Pengguna Lulusan pada Sistem Informasi Tracer Study Berbasis Web: Integration of Graduate User Evaluation Automation in Web-Based Tracer Study Information System - Silky Afina Saly; Mohammad Humam; Bayu Aji Santoso (Politeknik Negeri Malang, 2026)
This study develops a web-based Tracer Study information system that integrates three actors, admin, alumni, and graduate users in a single platform. The main contribution lies in an automated evaluation form distribution mechanism via email using a unique token-based link, allowing graduate users to submit assessments without registration or login. The system was built using the Agile Scrum methodology across four Sprints and evaluated through Black Box Testing and User Acceptance Testing (UAT) based on ISO 25010. Black Box Testing on 56 test cases covering all system modules yielded a 100% pass rate, including critical scenarios such as automated email delivery and token validation. UAT conducted with 35 respondents (3 admin staff and 32 alumni) produced an overall acceptance score of 83.80%, categorized as Very Feasible (≥81%). The Functional Suitability aspect achieved the highest score at 84.19%, indicating that the system features are complete and appropriate for institutional Tracer Study needs.